Extraction of underwater fragile artifacts: research status and prospect - Xue-Qiang Chen; Ke Xia; Wenjing Hu; Ming Cao; Kai Deng; Shiqiang Fang (Heritage Science, 2022)
Abstract There are still many difficulties in the recovery and long-term preservation of underwater archaeological artifacts, in situ preservation should be the first choice before further procedures are considered. However, the materials, preservation status, and preservation environment of underwater artifacts are diverse, resulting in many fragile artifacts facing difficult situations. In order to prevent serious damage, it is a safe protective strategy to preserve them in a controlled environment for a long time after excavation. Extraction and transfer of fragile cultural relics are vital parts of this strategy. Due to the complexity of the underwater environment and the vulnerability of fragile artifacts, safety in extraction and transfer still faces enormous challenges. Researchers have developed new materials and technologies to tackle this problem. This paper focuses on introducing and developing prospects to different preservation techniques for fragile artifacts from underwater sites.